MENGUNGKAP KESUKSESAN: PERUMUSAN STRATEGI UNTUK YOGA BARN UBUD BERDASARKAN ULASAN TRIPADVISOR DAN ANALISIS SWOT - Ida Ayu Kartika Maharani; Ni Komang Sudarningsih (UHN IGB Sugriwa Denpasar, 2023)
This study aims to formulate strategies for Yoga Barn in Ubud, Bali, amidst increasingly stiff competition and changing consumer needs. With the rising popularity of yoga and the proliferation of content on digital platforms, many yoga studios struggle to maintain their market position. In this context, Yoga Barn faces multiple challenges, including increasingly selective and quality-oriented consumer demands, as well as pressure from emerging new studios and expanding large studio networks. The research methodology involves content analysis of 830 customer reviews on Tripadvisor, analyzed using NVivo 7 software to identify and categorize key themes as a basis for SWOT analysis. Based on the findings, this study offers strategic recommendations for Yoga Barn. These include focusing on standardizing instruction through advanced teacher training, leveraging technology to improve scheduling and booking systems, and controlling the pace of expansion to ensure sustained service quality by reviewing and adjusting growth policies in line with capacity and customer needs.